Management of orthopaedic surgery in rare bleeding disorders. (10th March 2014) - Siboni, S. M.; Biguzzi, E.; Pasta, G.; Mannucci, P. M.; Mistretta, C.; Fantini, N. N.; Solimeno, L. P.; Peyvandi, F.
Summary: Knowledge regarding the management of orthopaedic surgery in patients with rare bleeding disorders (RBDs) is limited. Retrospective data collection and analysis of 35 orthopaedic procedures (6 minor and 29 major) carried out in 22 patients with RBD between 1982 and 2013. These surgeries were performed using heterogeneous regimens of hemostatic therapy, except for seven procedures performed with no hemostatic treatment in four patients with mild factor deficiency. Of the 28 procedures carried out with hemostatic treatment, nine (32%) were performed using replacement therapy with dosages of concentrates of the deficient factor aimed to achieve perioperative plasma levels judged to be compatible with hemostasis; three (11%) using factor replacement therapy associated with fresh frozen plasma (FFP); four (14%) using recombinant activated factor VII; four (14%) using virus inactivated plasma alone; three (11%) using virus inactivated plasma associated with desmopressin; one (4%) using FFP alone; and four (14%) procedures using tranexamic acid alone. Bleeding complications occurred in 7 of 35 procedures (20%) involving five patients. Prophylaxis of venous thromboembolism was performed only in one case with no excessive bleeding, but two patients not on thromboprophylaxis developed superficial thrombophlebitis. A satisfactory control of hemostasis was achieved in most patients. In some of those characterized by mild factor deficiency (FVII, FXI) hemostatic treatment could be avoided in some instances. The control of hemostasis combined with an adequate surgical technique is needed for the successful outcome of orthopaedic surgery in RBDs that requires the involvement of specialized haemophilia centres.